FROM KNOWLEDGE CATHEDRALS TO NETWORKED CO-CREATION: PUBLIC LIBRARIES, TRUST AND THE KNOWLEDGE ECONOMY - Wyatt, Danielle Ray; Leorke, Dale (AoIR Selected Papers of Internet Research, 2019)
Since the mid-nineteenth century, public libraries have been trusted sites of information. They have retained this public trust even as the networked society and digital technologies have profoundly changed the status and function of information in social and economic life. Information super-abundance, ‘platform capitalism’ and the rise of ‘big data’ have made information a currency within increasingly intersecting processes of commercial exchange, governance, surveillance and self-expression. Libraries are not on the sidelines of this shift. As media centres and information managers, they have supported users to navigate how information is distributed and accessed. They are also actively shaping how information is put-to-use, reconfiguring their service delivery around user-centred models emphasising participation and co-creation, user experience, pleasure, innovation, and peer-to-peer learning. This paper explores the tensions at the heart of the library’s continued status as a site of trusted information. Using a theoretically contextualized ethnographic methodology, the paper discusses how libraries perform as infrastructures of trust in the knowledge economy. Part one contextualises the library’s altered relation to information within its physical transformation as an institution. Part two draws upon interviews with Australian library professionals to drill down into the range of ways libraries perform informational trust at a time of systemic mistrust. Our findings reveal that many of these institutional performances of trust are non-equivalent, suggesting that we need to develop new thinking around the trust infrastructures we need in an information-abundant, entrepreneurialist culture.